Perbandingan Penggunaan Teknik Diversity pada Jaringan Gelombang Mikro di Lingkungan Danau - Syahrul Hidayat Triwibowo; Eka Wahyudi; Solichah Larasati (Departemen Teknik Elektro dan Teknologi Informasi, Fakultas Teknik, Universitas Gadjah Mada, 2019)
Microwave communication system is often implemented as a network cellular backhaul, due to its simplicity of installation and capability to reach remote areas which are difficult to reach using fiber optics. This paper compares themicrowave network with frequency diversity and space diversity technique in the lake area using Pathloss 5.0, using two sites, site Mongal and site Bintang in Aceh. These two sites are located in two cities separated by a Lake, so it doesn’t support wireline communications. Therefore, wireless communication is needed on site Mongal and site Bintang. Availability of the system without diversity optimization is 99.9554%. Using frequency diversity with frequency difference of 460 MHz, 920 MHz, and 1,380 MHz and using space diversity with space of 0.9 meter, 1.7 meter, and 2.6 meter, best availability of 99.9977% is obtained. The best availability is obtained using space diversity withmaximum spacing of 2.6 meter under the main antenna.